Pengembangan Video Pembelajaran Interaktif Berbasis Quizizz tentang Budaya Toleransi dan Keragaman di SMK 50 Jakarta - Muhammad Novry Ramadhan; Muhammad Nathan; Marseli Nurul Alifya; Mufid Irsyad; Valerina Rusmana Putri (CV Putra Publisher, 2025)
This study aims to develop an interactive learning video based on Quizizz focusing on cultural tolerance and diversity at SMK 50 Jakarta. The research employed the Research and Development (R&D) method using the ADDIE development model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The validation process involved two content experts and two media experts, with the Aiken Index used to assess the product's validity. The results indicated that the instructional video achieved a high level of validity, with an average Aiken Index of 0.915 for content experts and 0.87 for media experts. The video incorporates interactive quizzes through the Quizizz platform, designed to foster active student participation and improve their understanding of tolerance values and cultural diversity. This product is expected to serve as an innovative and effective solution for learning in multicultural educational settings, contributing to the development of tolerance attitudes among vocational high school students.